Novel Genomic Regions Linked to Ascochyta Blight Resistance in Two Differentially Resistant Cultivars of Chickpea - Alo, Fida; Rani, Anupalli Roja; Baum, Michael; Singh, Sarvjeet; Kehel, Zakaria; Rani, Upasana; Udupa, Sripada; Al-Sham’aa, Khaled; Alsamman, Alsamman M.; Istanbuli, Tawffiq; Attar, Basem; Hamwieh, Aladdin; et al. (Frontiers in Plant Science, 2022)
Ascochyta blight (AB) caused by the fungal pathogen Ascochyta rabiei is a devastating foliar disease of chickpea (Cicer arietinum L.). The genotyping-by-sequencing (GBS)-based approach was deployed for mapping QTLs associated with AB resistance in chickpea in two recombinant inbred lines populations derived from two crosses (AB3279 derived from ILC 1929 X ILC 3279 and AB482 derived from ILC 1929 X ILC 482) and, tested under six different environments. Twenty-one different genomic regions linked to AB resistance were identified on regions CalG02 and CalG04 in both populations AB3279 and AB482. These regions contain 1,118 SNPs significantly associated with AB resistance (p ≤ 0.001), which explained 11.2 to 39.3% of the phenotypic variation (PVE). Nine of the AB resistance associated genomic regions were newly detected in this study, whilst twelve regions were known from previous AB studies. The proposed physical map narrows down AB resistance to consistent genomic regions identified across different environments. Gene ontology (GO) assigned these QTLs to 319 genes, many of which were associated with stress and disease resistance, with most important genes belonging to resistance gene families including Leucine-Rich Repeat (LRR) and transcription factors families. Our results indicate that the flowering-associated gene GIGANTEA is a possible key factor in AB resistance in chickpea. The results have identified the AB resistance-associated regions on the chickpea physical genetic map and allowed for the identification of associated markers which will help in breeding for AB resistant varieties.